Late onset acrodermatitis enteropathica. - Garofalo, L. (European Journal of Pediatric Dermatology, 2012)
A little girl of 2.4 years came for examination from the Department of Pediatrics where she was hospitalized for stomatitis. The child had mild scaling lesions around the mouth and nails, on the feet and buttocks, arisen for a few days. The presence of thyroiditis with euthyroidism and of psoriasis in her family history led us to the diagnosis of suspected psoriasis. We observed again the child after two months with clear-cut, burn-like lesions mainly affecting the perioral region (Fig. 1), buttocks, hands, ankles, elbows and with hair loss. The clinical diagnosis of late onset acrodermatitis enteropathica was confirmed by low serum levels of zinc, 38.7 mcg/100 ml (n.v.: 108 +/-15) and alkaline phosphatase and by the response to treatment with zinc sulfate (25 mg 3 times daily) that healed quickly all the skin lesions (Fig. 2).